2022
DOI: 10.1186/s12872-022-02843-y
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of pericoronary adipose tissue with coronary artery disease and left ventricular function

Abstract: Objective We sought to investigate the correlation of pericoronary adipose tissue with coronary artery disease and left ventricular (LV) function. Methods Participants with clinically suspected coronary artery disease were enrolled. All participants underwent coronary computed tomography angiography (CCTA) and echocardiography followed by invasive coronary angiography (ICA) within 6 months. Pericoronary adipose tissue (PCAT) was extracted to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
(63 reference statements)
1
3
0
Order By: Relevance
“…Other studies had similar results as our data regarding correlation of EAT thickness and PCFT and obstructive CAD [14,15]. However, You et al [16] reported that there was no correlation between PCFT and CAD severity. A possible explanation for this inconsistency might be a different study design and measurement methods.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies had similar results as our data regarding correlation of EAT thickness and PCFT and obstructive CAD [14,15]. However, You et al [16] reported that there was no correlation between PCFT and CAD severity. A possible explanation for this inconsistency might be a different study design and measurement methods.…”
Section: Discussionsupporting
confidence: 89%
“…Wen D et al also reported that PCAT CT attenuation, but not volume, was related to the haemodynamic significance of coronary artery stenosis [ 19 ]. You D et al reported that risk factors for coronary artery disease and the Gensini score had no association with PCAT volume [ 37 ]. The radiodensity of fat tissue may become a more sensitive imaging marker than adipose tissue volume [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…While several common risk factors predispose to both obesity and atherosclerosis, for a long time, these two diseases were viewed as parallel, simultaneously developing, but mechanistically independent. However, alterations in adipose tissue function in atherosclerosis recently started to draw significant attention ( 34 36 ). Perivascular adipose tissue (PVAT) is especially interesting due to its proximity to the aortic wall ( Figure 1 ).…”
Section: Types Of Adipose Tissuementioning
confidence: 99%